Value of Adding Cisternostomy to Decompressive Hemicraniectomy in the Management of Traumatic Acute Subdural Hematoma Patients - Youssef, Omar; Ali, Taher M.; Anbar, Khaled; El-Shahawy, Osama; Enayet, Abdelrhman (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Surgical evacuation of acute subdural hematoma has remained the mainstay of the treatment for acute subdural hematoma (ASDH) in patients with progressive neurological deficits, increasing intracranial pressure (ICP), or significant mass effect. Cisternostomy entails opening the basal cisterns aiming to their opening to atmospheric pressure and therefore reducing the intraparenchymal pressure. AIM: We aimed to evaluate value of adding cisternostomy to decompressive craniotomy on outcome of traumatic ASDH patients. METHODS: Prospective study included 40 patients who presented to Cairo University hospital emergency department with traumatic acute subdural hematoma in the period between January 2018 and June 2019 and matching our inclusion criteria: Age from 12 to 65 years, traumatic acute subdural hematoma with thickness ≥ 10 mm or midline shift ≥ 5 mm, and Glasgow Coma Scale (GCS) on admission < 10, with no associated intraparenchymal hematoma ≥ 1 cm or severe comorbidities. Patients were randomized into one of two groups according to their order of coming. The first group patients were operated on by decompressive craniotomy (DHC) plus cisternostomy and the second group was operated on by decompressive craniotomy only. Glasgow Outcome Score (GOS) was used for outcome assessment. RESULTS: Outcome was better 2nd but not statistically significant – in the first group (DHC+ cisternostomy) in terms of mortality: 7/20 patients (35%) (p = 0.337) and median GOS: 3 (p = 0.337), compared to the second group (DHC only) in which mortality occurred in 10/20 (50%) and median GOS was 1. Adding cisternostomy to decompressive craniotomy increased surgery time with 35.5 minutes in average. In our study, older age and lower GCS on admission had significantly worse outcome. CONCLUSION: Adding cisternostomy to decompressive craniotomy in traumatic patients had better 2nd but not statistically significant outcome. Whether it should replace the routine decompressive craniotomy in these cases or not needs further larger clinical trials.